Prognostic role of miR-221 and miR-222 expression in cancer patients: a systematic review and meta-analysis - Ravegnini, Gloria; Lorenzo Bermejo, Justo; Hrelia, Patrizia; Terrazzino, Salvatore; Angelini, Sabrina (Cancers, 2019)
Background: A wealth of evidence has shown that microRNAs (miRNAs) can modulate specific genes, increasing our knowledge on the fine-tuning regulation of protein expression. miR-221 and miR-222 have been frequently identified as deregulated across different cancer types; however, their prognostic significance in cancer remains controversial. In view of these considerations, we performed an updated systematic review and meta-analysis of published data investigating the effects of miR-221/222 on overall survival (OS) and other secondary outcomes among cancer patients. A systematic search of PubMed, Web of Knowledge, and Cochrane Library databases was performed. Hazard ratios (HRs) and 95% confidence intervals (95% CIs) were used to assess the strength of association. Results: Fifty studies, analyzing 6086 patients, were included in the systematic review. Twenty-five studies for miR-221 and 17 studies for miR-222 which assessed OS were included in the meta-analysis. High expression of miR-221 and miR-222 significantly predicted poor OS (HR: 1.48, 95% CI: 1.14–1.93, p = 0.003 and HR: 1.90, 95% CI: 1.43–2.54, p < 0.001, respectively). Subgroup analysis revealed that the finding on miR-221 was not as robust as the one on miR-222. Furthermore, high miR-222 expression was also associated with worse progression-free survival and disease-free survival pooled with recurrence-free survival. Conclusions: The meta-analysis demonstrated that high expression of miR-222 is associated with poor prognosis in cancer patients, whereas the significance of miR-221 remains unclear. More work is required to fully elucidate the role of miR-221 and miR-222 in cancer prognosis, particularly in view of the limitations of existing results, including the significant heterogeneity and limited number of studies for some cancers.
Gesehen am 04.11.2019